2016
DOI: 10.1007/s00234-016-1646-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between functional connectivity and motor function assessment in stroke patients with hemiplegia: a resting-state functional MRI study

Abstract: Our results revealed an abnormal motor network after stroke and suggested that the FC could serve as a biomarker of motor function recovery in stroke patients with hemiplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 26 publications
9
78
0
Order By: Relevance
“…A more recent analysis of hemiplegic stroke patients examined the functional connectivity between ipsilesional M1 and the entire brain using resting state fMRI [53]. As expected, stroke altered functional connectivity and disrupted motor pathways (as compared to healthy controls).…”
Section: Neural Correlates Of MI and Clinical Implicationsmentioning
confidence: 98%
“…A more recent analysis of hemiplegic stroke patients examined the functional connectivity between ipsilesional M1 and the entire brain using resting state fMRI [53]. As expected, stroke altered functional connectivity and disrupted motor pathways (as compared to healthy controls).…”
Section: Neural Correlates Of MI and Clinical Implicationsmentioning
confidence: 98%
“…[Insert Table 1 here] Among the studies observing recovery without additional training, the dominant technique of connectivity measurement was fMRI (Cheng et al, 2012;Cheng et al, 2015;Golestani et al, 2013;Lee et al, 2015;Liu et al, 2016;Ovadia-Caro et al, 2013;Park et al, 2011;Rehme et al, 2011;Rosso et al, 2013;Wang et al, 2010;Xu et al, 2014;Yourganov et al, 2010). One study used MEG (Westlake et al, 2012) and one used EEG (Nicolo et al, 2015).…”
Section: Recovery Studiesmentioning
confidence: 99%
“…Five studies assessed connectivity during hand movement (Cheng et al, 2012;Cheng et al, 2015;Rehme et al, 2011;Rosso et al, 2013;Yourganov et al, 2010) and the remainder utilised the resting state paradigm (Golestani et al, 2013;Lee et al, 2015;Liu et al, 2016;Nicolo et al, 2015;Ovadia-Caro et al, 2013;Park et al, 2011;Wang et al, 2010;Westlake et al, 2012;Xu et al, 2014). The fMRI studies analysed FC based on the time series correlation matrix and reported specific regions, change, lateralization and FC density of regions connected with the region of interest (ROI) except Yourganov and colleagues https://mc.manuscriptcentral.com/revneuro Neurosciences 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P r e v i e w O n l y 9 (2010), who assessed the complexity measures of a covariance matrix basing on principal component analysis (PCA).…”
Section: Reported Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We have the assumption that the modulation of 11 neuroplasticity is one of the underlying reasons of motor function improvement. FC 12 could serve as a biomarker of motor function recovery in stroke [83], which depicts 13 the functional organization of the brain and neuroplasticity. The significant corre- 14 lation between motor function improvement and FC change indicated that iM1 and 15 contralesional BA6 could be regarded as the related areas to facilitate upper-limb 16 motor recovery after stroke.…”
mentioning
confidence: 99%